2008
DOI: 10.1103/physreve.78.017101
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cooperation in highly clustered scale-free networks

Abstract: We study the effect of clustering on the organization of cooperation, by analyzing the evolutionary dynamics of the Prisoner's Dilemma on scale-free networks with a tunable value of clustering. We find that a high value of the clustering coefficient produces an overall enhancement of cooperation in the network, even for a very high temptation to defect. On the other hand, high clustering homogeneizes the process of invasion of degree classes by defectors, decreasing the chances of survival of low densities of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 25 publications
(46 reference statements)
6
136
2
Order By: Relevance
“…Indeed, the graph corresponds to a random geometric graph [20], a network having the same P (k) as an ER random graph, but with a higher clustering coefficient. This latter feature leads to a further increment of the average level of cooperation, as it has been shown that a network with a high clustering coefficient promotes cooperation [21,22].…”
Section: Network Of Interactionsmentioning
confidence: 99%
“…Indeed, the graph corresponds to a random geometric graph [20], a network having the same P (k) as an ER random graph, but with a higher clustering coefficient. This latter feature leads to a further increment of the average level of cooperation, as it has been shown that a network with a high clustering coefficient promotes cooperation [21,22].…”
Section: Network Of Interactionsmentioning
confidence: 99%
“…While small-world networks are also known to support cooperative behaviors (Abramson and Kuperman, 2001;6 Tomassini et al, 2006;Vukov et al, 2008), it has been extensively reported that scale-free networks strongly enhance the survival of cooperation Santos et al, , 2006Gómez-Gardeñes et al, 2007. Different aspects related to social structure have been studied such as, for example, clustering (Assenza et al, 2008), robustness to suppression of nodes (Perc, 2009), the existence of distinct interaction and updating neighborhoods (Ohtsuki et al, 2007), as well as the interplay between social structure and other aspects such as diversity of reproduction rates (Szolnoki et al, 2008c) and payoff normalization (Tomassini et al, 2007;Szolnoki et al, 2008b). Besides features related to social structure, as spatial distance and heterogeneity in the number of connections, it is commonly accepted that relatedness of individuals, reputation and repeated interactions, allied to memory and recognition capacities, are also mechanisms that promote cooperative behaviors (Axelrod, 1984).…”
Section: Previous Workmentioning
confidence: 99%
“…It is known that the structure of the network is also a key factor in the evolution of behavior of agents. Later, a shift from evolutionary games on regular lattices to evolutionary games on complex networks was proposed [5], in particular on small world networks [6,7,8] and on scale-free networks [9,10,11]. Meanwhile, other games, such as Snowdrift (SD) [12], Stag-Hunt (SH) [13], and Public Goods games, have produced interesting results [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%